Assessment of Gingival Enlargement in Epileptic patients - A Retrospective study - MANOHARAN, SUHAS; DHARMAN, SREEDEVI; KUMAR S, ARAVIND (The journal of contemporary issues in business and government, 2020)
Epilepsy is a neurological disorder with recurrent seizures in patients due to underlying chronic disease.Medications taken by epileptics can cause gingival enlargement. Gingival enlargement is aesthetically undesirable and causes difficulty in mastication,speech. The aim of the study was to assess the association of age, gender in epileptic patients with gingival enlargement. A retrospective study for presence of gingival enlargement in epileptic patients was reviewed from patient records and analysing the case sheets between June 2019 and March 2020 in dental outpatient department.Age groups of patients involved in the study are 20-35 years,35-50 years and 50-65 years. Patient age,gender,type of gingival enlargement were also collected. Excel tabulation was done and results obtained from SPSS version 20. Statistical test performed was chi square analysis to find the association of gingival enlargement types with age,gender of epileptic patients. 118 case sheets were studied out of which 70 were females and 48 were Males.Only 8% of the total study group showed epilepsy related drug induced gingival enlargement.Gingival enlargement of generalised type was seen commonly in males(3.42%)0.063(p>0.05) statistically not significant,in the age group of 20-35 years(2.85%)P value - 0.696(p>0.05),not statistically significant and localised among both genders in the age group of 20-35 years(1.89%).Periodontal disease was more in generalised gingival enlargement but not significantly associated,p value- 0.788(p>0.05),not statistically significant.Within the limits of the study ,a small percentage of epileptic patients had drug induced gingival enlargement.Males showed comparatively higher distribution of generalised gingival enlargement in epileptic patients. Periodontal pathologies were common in epileptic patients with gingival enlargement.